Efektivitas Asosiasi Inokulan Campuran Bakteri Rhizosfer dengan Tanaman Jagung Varietas Srikandi pads Tanah Latosol Lampung - Gandanegara, S.; Sugoro, I.; Slamet, S. (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTThe Effectiveness of Rhizospheric Bacteria Mix Inoculant Associated with Maizein Latosol Lampuog Soil. Two greenhouse experiments were carried out to evaluate theeffectiveness of Plant Growth Promoting Rhizobacteria (PGPR) ino-culants on plant growthof maize. In the first experiments, eleven single isolates were screened for associationeffectiveness with maize. Inoculation improved plant perfomance by increasing roots, shootsand total plant dry weight. Five isolates with the increase of plant dry weight ranging from 27-47% over control were then selected for mixed inoculants. In the second experiment, tenmixed inoculants consisted of 3 single isolates were evaluated on plant growth, N plant yield,and N derived from fertilizer and contribution from fixation. The later parameter was.determined by